Mediating effects of body mass index, physical activity, and emotional distress on the relationship between short sleep and cardiovascular disease. Issue 37 (September 2018) - Seixas, Azizi A.; Vallon, Julian; Barnes-Grant, Andrea; Butler, Mark; Langford, Aisha T.; Grandner, Michael A.; Schneeberger, Andres R.; Huthchinson, Jhenelle; Zizi, Ferdinand; Jean-Louis, Girardin
Abstract : Abstract: The current study investigated the mediating effects of body mass index (BMI), physical activity, and emotional distress on the association between short sleep duration (<7 hours per 24-hour period) and cardiovascular disease (CVD) and risk factors. We used data from the National Health Interview Survey, an ongoing nationally representative cross-sectional study of noninstitutionalized US adults (≥18 years) from 2004 to 2013 (N = 206, 049). Participants provided information about anthropometric features (height and weight), sociodemographic factors, health behaviors (smoking and physical activity), emotional distress, and physician-diagnosed health conditions, including hypertension, coronary heart disease, diabetes, heart attack, stroke, kidney disease, and cancer. Structural equation modeling was used to assess the mediating effects of physical activity, BMI, and emotional distress on the relationship between short sleep and CVDs and risk factors (coronary heart disease, hypertension, diabetes, chronic kidney disease, heart attack, and stroke). Of the sample, 54.7% were female, 60.1% identified as white, 17.7% as Hispanic, and 15.4% as black. The mean age of the respondents was 46.75 years (SE = 0.12), with a mean BMI of 27.11 kg/m 2 (SE = 0.02) and approximately 32.5% reported short sleep duration. The main relationship between short sleep and CVD and risk factors was significant (β = 0.08, P < .001), as was the mediated effect via BMI (indirect effect = 0.047, P < .001), emotional distress (indirect effect = 0.022, P < .001), and physical activity (indirect effect = -0.022, P = .035), as well as after adjustment for covariates, including age, race, sex, marital status, and income: short sleep and CVD (B = 0.15; SE = 0.01; P < .001), BMI (B = 0.05; SE = 0.00; P < .001), emotional distress (B = 0.02; SE = 0.00; P < .001), and physical activity (B = 0.01; SE = 0.00; P < .001). Our findings indicate that short sleep is a risk factor for CVD and that the relationship between short sleep and CVD and risk factors may be mediated by emotional distress and obesity, and negatively mediated by physical activity.